2016
DOI: 10.1038/srep25754
|View full text |Cite
|
Sign up to set email alerts
|

SARS coronavirus papain-like protease induces Egr-1-dependent up-regulation of TGF-β1 via ROS/p38 MAPK/STAT3 pathway

Abstract: SARS coronavirus (SARS-CoV) papain-like protease (PLpro) has been identified in TGF-β1 up-regulation in human promonocytes (Proteomics 2012, 12: 3193-205). This study investigates the mechanisms of SARS-CoV PLpro-induced TGF-β1 promoter activation in human lung epithelial cells and mouse models. SARS-CoV PLpro dose- and time-dependently up-regulates TGF-β1 and vimentin in A549 cells. Dual luciferase reporter assays with TGF-β1 promoter plasmids indicated that TGF-β1 promoter region between −175 to −60, the Egr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 33 publications
1
109
0
1
Order By: Relevance
“…Our prior study demonstrated SARS-CoV PLpro triggering the TGF-β1 production in vitro and in vivo that linked with up-regulating the expression of pro-fibrotic proteins (vimentin and glial fibrillary acidic protein) (Li et al, 2016b). This study assesses possible effects and mechanisms of SARS-CoV PLpro-induced TGF-β1 upregulation on the expression of Type I collagen.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our prior study demonstrated SARS-CoV PLpro triggering the TGF-β1 production in vitro and in vivo that linked with up-regulating the expression of pro-fibrotic proteins (vimentin and glial fibrillary acidic protein) (Li et al, 2016b). This study assesses possible effects and mechanisms of SARS-CoV PLpro-induced TGF-β1 upregulation on the expression of Type I collagen.…”
Section: Introductionmentioning
confidence: 95%
“…Human alveolar basal epithelial A549 cells grew in Dulbecco's Modified Eagle's Medium (HyClone Laboratories) and were transfected with control vector pcDNA3.1/His C (Invitrogen), or pSARS-PLpro containing SARS-CoV PLpro gene, as described in our prior reports (Li et al, 2011(Li et al, , 2012(Li et al, , 2016a(Li et al, , 2016b. In addition, pSARS-PLpro (H273A) that had the alanine substitution for histidine at position 273 by Ala within PLpro gene was constructed using PCR-based sitedirected mutagenesis with a mutated primer pair (5′-GGTAACT ATC-AGTGTGGTGCTTACACTCATATAACTGCTAAG-3′ and 5′-CTTAGCAGT TATATGAGTGTAAGCACCACACTGATAGTTACC-3′).…”
Section: Cell Culture and Transient Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, it has been widely accepted that a relatively high level of ROS causes redox imbalance, which induces cell apoptosis or necrosis under a wide variety of physiological and pathological conditions . Recent studies have proven that ROS can activate MAPKs, and apoptotic cell death induced by ROS is mediated by the p38MAPK pathway in lung and renal cells. Interestingly, in the kidney of CKD rats, the levels of ROS were markedly increased, the activities of anti‐oxidative enzymes, SOD and GSH‐Px, were significantly decreased, and ROS could induce apoptosis …”
Section: Introductionmentioning
confidence: 99%